1987
DOI: 10.1096/fasebj.1.6.3315807
|View full text |Cite
|
Sign up to set email alerts
|

Free radical tissue damage: protective role of antioxidant nutrients 1

Abstract: Highly reactive molecules called free radicals can cause tissue damage by reacting with polyunsaturated fatty acids in cellular membranes, nucleotides in DNA, and critical sulfhydryl bonds in proteins. Free radicals can originate endogenously from normal metabolic reactions or exogenously as components of tobacco smoke and air pollutants and indirectly through the metabolism of certain solvents, drugs, and pesticides as well as through exposure to radiation. There is some evidence that free radical damage cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
456
1
21

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,057 publications
(487 citation statements)
references
References 25 publications
9
456
1
21
Order By: Relevance
“…39) Free radicals formed during the reduction of O 2 , such as peroxy-, hydroxy-, and superoxide radicals, are known to cause cell damage directly or indirectly. 40) Previous animal studies show that persistent hyperglycemia causes increased production of reactive oxygen species through glucose autooxidation and NEG, which in turn causes increased oxidative stress. 41) GSH, the most important biomolecule against chemically induced toxicity, can participate in the elimination of reactive intermediates by reduction of hydroperoxides in the presence of GP x .…”
Section: Discussionmentioning
confidence: 99%
“…39) Free radicals formed during the reduction of O 2 , such as peroxy-, hydroxy-, and superoxide radicals, are known to cause cell damage directly or indirectly. 40) Previous animal studies show that persistent hyperglycemia causes increased production of reactive oxygen species through glucose autooxidation and NEG, which in turn causes increased oxidative stress. 41) GSH, the most important biomolecule against chemically induced toxicity, can participate in the elimination of reactive intermediates by reduction of hydroperoxides in the presence of GP x .…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous sources of ROS in aerobic mammalian cells are the mitochondrial electron carriers and enzymes. Representative external sources include redox cycling drugs, radiation, and various lifestyle and environmental influences, such as smoking, drinking alcohol, excessive exercise, pollution, and overexposure to the sun (Machlin and Bendich, 1987;Dizdaroglu, 1993). The highlyreactive superoxide radical and hydrogen peroxide may be toxic to cells by a direct attack at the molecular level, or indirectly by generating secondary reactive species such as the hydroxyl radical (Brenneisen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, in other studies, this association could not be confirmed (7)(8)(9)(10). Antioxidant defense is achieved by additive or synergistic action of enzymes and antiox-idant nutrients (11,12). Selenium and vitamin E in particular appear to have overlapping and partly compensative functions (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%